STRATEGI INTEGRASI NILAI PENDIDIKAN AGAMA ISLAM PADA PROGRAM ADIWIYATA DI SMP N 23 SEMARANG - Ahmad Munarun; Fentika Zahra Qoirunnisa; Nita Yuli Astuti (IAIN Madura, 2025)
The integration of Islamic Education (PAI) values into the Adiwiyata program at SMP N 23 Semarang creates a synergy between religious and environmental education. This study aims to analyze strategies for integrating PAI values into the Adiwiyata program to enhance students' environmental awareness. A qualitative research method was employed through in-depth interviews, observations, and documentation involving teachers, students, and the school principal. The findings reveal that the development of an integrated curriculum, participatory activities, teacher training, community collaboration, and the use of technology effectively increase students' awareness of environmental issues. These findings contribute significantly to creating a holistic educational approach that strengthens students' religious character and environmental responsibility.